Inhibition of quorum sensing in Pseudomonas aeruginosa PAO1 by Phyllanthus amarus Extract and Baicalein / Kumutha Priya a/p Munusamy - Kumutha Priya, Munusamy (2017)
Quorum sensing (QS) is a sophisticated signalling system employed by bacteria to regulate a population wide gene expression with the utilization of diffusible chemical signalling molecules known as autoinducers. This system is widely exploited by both Gram-negative and Gram-positive bacteria to control a wide array of physiological functions. Pseudomonas aeruginosa is one of the infamous bacteria that employ the QS system to regulate the expression of virulence factors such as biofilm formation, antibiotic resistance, and the production of toxins, proteases, and haemolysins. Hence, this study aimed to determine the mode of action of QS inhibitors against P. aeruginosa using crude plant extracts and synthetic compound. A total of 15 Malaysian endemic plants were selected and screened for their anti-quorum sensing properties using Chromobacterium violaceum CVO26. Subsequently, only Phyllanthus amarus was chosen for further screenings. The methanolic extract of P. amarus successfully inhibited the short and long chain AHL activities when screening using Escherichia coli bioluminescence biosensors. The extract also attenuated P. aeruginosa QS-controlled virulence factors, namely, swarming, pyocyanin production, and the expression of the cytotoxic lectin. This is the first report of anti-quorum sensing activity of P. amarus against several QS-controlled virulence factors of P. aeruginosa. Our work also focussed on synthetic compound that are of plant origin. Baicalein, a flavone was chosen for the study. Baicalein exhibited promising anti-quorum sensing activities during preliminary screenings using E. coli biosensors by inhibiting bioluminescence produced. Baicalein, at low concentrations, also significantly inhibited several virulence factors of P. aeruginosa without impairing its’ growth. These significant findings have prompted us to divulge the global gene expression of P. aeruginosa when exposed to these two compounds by using RNA-sequencing technology. Bioinformatics analysis has given us insights into the mechanism of QS-inhibition by baicalein. It is hoped that the findings from this research will be of use in a pharmacological perspective especially in the current crisis of the emergence of new multidrug resistant organisms (MDRO).